Pelatihan Penentuan Harga Pokok Penjualan Buket Snack dan Buket Bunga Jemaat Wanita di Gereja Kristen Indonesia pada Kota Surabaya - Memarista, Gesti; Gestanti, Lila (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
Accurate determination of the Cost of Goods Sold (COGS) is crucial in business management, particularly for micro and small enterprises that produce snacks and flower bouquets. The limited understanding of COGS calculation methods often hinders business development and the establishment of competitive selling prices. This program is designed to offer training for 16 female congregation members at the Gereja Kristen Indonesia Surabaya in systematically calculating COGS. The activity was conducted from December 1, 2024, to February 16, 2025. The training method includes theoretical presentations, interactive discussions, and simulations of COGS calculations based on raw material costs, labor costs, and overhead expenses. Additionally, participants were guided on determining reasonable profit margins to ensure their products remain competitive in the market. Overall, participants' average understanding improved from 1.763 in the pre-test to 4.200 in the post-test, reflecting a 138.23% increase. This result shows that the training provided has significantly increased participants' knowledge of COGS and its application in determining the selling price of products. This training is expected to have a positive impact on the sustainability of women's businesses at GKI Surabaya, increasing profitability and promoting economic independence. Similar programs could be expanded to include advanced topics such as marketing strategies and financial management, further supporting community-based economic growth.